A double‐edged sword: Unrecognized cryptic diversity and taxonomic impediment in Eois (Lepidoptera, Geometridae). (7th April 2021) - Moraes, Simeão de Souza; Murillo‐Ramos, Leidys; Machado, Patrícia A.; Ghanavi, Hamid R.; Magaldi, Luiza M.; Silva‐Brandão, Karina L.; Kato, Massuo J.; Freitas, André V. L.; Wahlberg, Niklas
Abstract: The genus Eois Hübner (Geometridae: Larentiinae) comprises 254 valid species. Being a hyperdiverse genus, Eois potentially includes many undescribed cryptic species and embodies a problematic taxonomic scenario. The actual diversity of Eois is greatly underestimated and the Neotropical fauna needs to be well known since it figures as one of the most threatened terrestrial ecosystem. In the present study, we compare three species delimitation methods to highlight the hidden diversity within a subset of Eois species: Automatic Barcode Gap Discovery, Bayesian Poisson Tree Processes and Multi‐Rate Poisson Tree Processes. Our results point to an increase up to 176% in the currently valid species number. The hypothesis of cryptic diversity is corroborated by morphological characters within some species complexes. For complexes comprising species of Brazilian fauna, we provide a preliminary taxonomic assessment. Additionally, we found no congruence among the three delimitation methods for some species complexes, which indicates the importance of species and locality sampling as well as the previous alpha taxonomic knowledge in avoiding result bias. In this sense, we tried to standardize the identification provided for the Genbank sequences used in most relevant publications for Eois, in order to minimize biases and maximize the replicability of analyses in future studies. Moreover, we stress the importance of an integrative taxonomic approach for cryptic species discovery approach by employing both morphological attributes and life history to corroborate molecular analysis.